Photothermal oxidative dehydrogenation of propane to propylene over Cu/BN catalysts - Sun, Shaoyuan; Zhao, Manqi; Liu, Huimin; Li, Dezheng; Lei, Yiming (Frontiers in Chemistry, 2024)
Oxidative dehydrogenation of propane (ODHP) is a reaction with significant practical significance. As for the industrial application of ODHP, it is challenging to achieve high activity and high propylene selectivity simultaneously. In this study, to overcome this obstacle, we designed a series of Cu/BN catalysts with unique morphologies for establishing a photothermal ODHP system with high efficiency and selectivity. Characterization and evaluation results revealed that Cu/BN-NS and Cu/BN-NF with enlarged specific surface areas exhibited higher catalytic activities.The localized surface plasmon resonance (LSPR) effect of Cu nanoparticles further enhanced the photothermal catalytic performances of Cu/BN catalysts under visible light irradiation. To the best of our knowledge, it is the first time to establish a BNbased photothermal ODHP catalytic system. This study is expected to pave pathways to realize high activity and propylene selectivity for the practical application of ODHP.